Rational Choice and Benchmarking of Madrasah Aliyah Accreditation Quality in the Serang Urban Area - Nurhalim Nurhalim; Encep Syarifudin; Muhajir Muhajir (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2025)
Urban communities tend to reason about the choice of quality education. The research aims to analyse the community's rational choices regarding the quality of madrasas and determine the perception of benchmarking of madrasah accreditation in Serang City. The research uses a qualitative method with a case study approach at Madrasah Aliyah, Serang City. Data collection was done through interviews with informants from madrasah managers, parents of students, and madrasah supervisors, and data analysis was done using descriptive and triangulation techniques. The study results found that the rational choice of urban communities for the quality of madrassas in Serang City was influenced by academic, social, and cultural factors. The sensible choice lies in the superiority of religious education, but it offers quality public education as a holistic option, encompassing academic, moral, and spiritual dimensions. Public perception is influenced by the ability of madrasas to meet the criteria of the National Accreditation Board, which describes the strengths and weaknesses in improving the quality of education. The benchmarking process has a positive influence on enhancing the accreditation and quality of madrasas. The perception of the Head of the Madrasah regarding managerial changes and educational quality standards is an essential indicator for parents and supervisors to improve the quality of continuous education. The research implies that the more rational the choice of the quality of madrasah accreditation, the more it will increase the perception of benchmarking of Islamic educational institutions. This research is limited to Madrasah Aliyah Negeri in Serang City.